Cost of diabetes mellitus and associated factors – an institutional cross-sectional study in Ghana - John Azaare; Andrew Mpagwuni Ziblim; Emmanuel Akolgo Abanga; Daudi Yeboah; Abdulai Abubakari (BMC Health Services Research)
Abstract Background Diabetes mellitus, like many other chronic diseases, is costly to manage and poses a substantial economic burden on individuals directly and indirectly. In this paper, we studied the associations between cost of diabetes and socio-demographic characteristics. Methods This was a cross-sectional cost-of-illness study that employed systematic random sampling. We collected data from 385 respondents at the Tamale Teaching Hospital of Ghana between June and August of 2023. Prevalence-based costing and the human capital approach were employed to arrive at total cost of illness. Regression analysis was used to find associations between sociodemographic characteristics of the respondents and the total cost of illness. Results The mean total cost of diabetes mellitus per year is $290.44. Mean direct annual cost of illness per year is $159.70 representing 54.99% of the total cost while the mean indirect annual cost per patient is $130.72. Being male (B = 0.42, 95% CI 0.02–0.82; p = 0.039), living in an urban area (B = - 1.05 95% CI - 1.58 – - 0.53; p = 0.000), having a longer duration of illness (B = 0.04, 95% CI 0.003–0.07; p = 0.032), and having the complications of diabetic retinopathy (B = 0.42, 95% CI 0.02–0.82; p = 0.041) and stroke (B = 1.26, 95% CI 0.52–2.00; p = 0.001) were statistically significant in association with total cost of illness. Conclusions Various demographics with diabetes carry different dynamics in terms of cost burden. We recommend a tailored approach to care for individuals with diabetes mellitus and their families as a protection against catastrophic health care expenditure that could result from a high cost of illness.